The dilemma of levothyroxine replacement timing: comparison of bedtime versus early-morning replacement of levothyroxine in post total thyroidectomy patients - Ferdinant, Jabamalai; Rao, Smitha S.; Chandru, Kahrin Rakesh; Zahir, Hussain (International Surgery Journal, 2019)
Background: Following total thyroidectomy levothyroxine replacement is imperative and required lifelong. There are many studies done to assess the effectiveness of levothyroxine administration in hypothyroid patients with intact thyroid gland. This study was intended to evaluate if bedtime dose of levothyroxine is same as early-morning replacement of levothyroxine in post total thyroidectomy patients. Methods: A randomized study was conducted on patients who underwent total thyroidectomy for benign thyroid disorders from September 2017 to August 2018 at endocrine surgery department in a tertiary care institute (South India). Patients were randomly assigned into two groups by chit method, Group A received levothyroxine early morning one hour before food and the Group B received levothyroxine at bedtime two hours after food up to 3 months. 6 weeks and 12 weeks fT4 (freeT4) and TSH (thyroid stimulating hormone) were measured during follow up. Results: A total of 123 patients were recruited and randomized into either of the study groups. 58 patients in Group A and 53 patients in Group B were considered for statistical evaluation. At 6th and 12th week assessment mean TSH level of early-morning group and bedtime group had no statistical difference. At 6th week assessment, mean fT4 level of bedtime group was insignificantly than the early morning group. At 12th week assessment, mean fT4 level of bedtime group was higher than early-morning group, and the difference was also statistically significant (p=0.0005). Conclusions: Clinicians may consider prescribing levothyroxine at bedtime as an alternative to the conventional morning dose.